Wheeled hopping robot with combustion-powered actuator. (11th January 2018) - Miao, Zhihuai; Mo, Jixue; Li, Gang; Ning, Yinghao; Li, Bing
While exploring complex environments, conventional mobile robots can overcome obstacles of limited height and jumping robots can overcome obstacles several times their own size. When jumping motion and wheeled or tracked motion are combined to form a composite motion, robots have even better ability to traverse rugged terrain. Therefore, we designed a wheeled hopping robot with a novel combustion-powered actuator and carried out structural design and experimental studies. The combustion-powered actuator has a unique inlet scheme and good sealing performance and is easy to install. The jump height equation was obtained by analyzing the combustion process. With the help of orthogonal array design methods, the factors that affect the wheeled hopping robot's jumping height were analyzed to improve its key design parameters and optimize its jumping performance. Finally, experiments were performed with the actuator and the wheeled hopping robot. When the stoichiometric ratio of the mixed fuels nears complete combustion, the combustion-powered actuator can jump 7.5 m high with a payload of 3.75 kg and its own weight of 1.25 kg, and the wheeled hopping robot can jump 4.5 m high with a payload of 6 kg. Evaluating the robot's performance in terms of energy efficiency reveals that it has a significant jumping advantage.